Improving the assessment of the economic impact of parasitic diseases and of their control in production animals - Perry, Brian D.; Randolph, Thomas F. (Elsevier, 1999)
This paper reviews the ways in which the economic impact of parasitic diseases of production animals have been evaluated. It then discusses the shortfalls of such studies as well as the opportunities for improving the quality of economic impact assessments and their value to decision makers in the future. The paper first identifies the impacts that are specific to parasitic diseases. It then goes on to review the abundant literature on estimating the total costs of diseases. The authors argue that this approach severely limits the opportunity for economic assessments to aid decisions in disease control and research. The paper then reviews the literature on studies of avoidable costs, before discussing ways in which economic impact assessments can be enhanced. These issues include greater emphasis on incorporating the lost productivity potential caused by parasitic diseases, greater emphasis on valuing actual rather than intended control measures, and greater emphasis on quantifying the productivity effects at the societal level, particularly in the developing world.